The green sea turtle - Müller, Isabel (Illustrator) (NorthSouth, 2014)
Follows one green sea turtle for twenty years as it travels around the Indian Ocean and returns to its birthplace on Raine Island to lay eggs that will produce a new generation of sea turtles.